Risankizumab for the Treatment of Moderate to Severe Psoriasis: Impact on Health-Related Quality of Life and Psychological Wellbeing - Gracia-Cazaña T; Bernal-Masferrer L; Morales-Callaghan AM; Almenara-Blasco M; Gilaberte Y (Dove Medical Press, 2023)
Tamara Gracia-Cazaña,* Laura Bernal-Masferrer,* Ana María Morales-Callaghan, Manuel Almenara-Blasco, Yolanda Gilaberte Dermatology Service, Hospital Miguel Servet, IIS Aragon, Zaragoza University, Zaragoza, Spain*These authors contributed equally to this workCorrespondence: Tamara Gracia-Cazaña, Dermatology Service, Hospital Miguel Servet, Zaragoza, Paseo Isabel la Católica 1-3, P.O.Box: 50009, Zaragoza, Spain, Tel +34 6657571403, Email tamgracaz@gmail.comAbstract: Biologic treatments are increasingly being used in the management of moderate to severe plaque psoriasis (PSO). Risankizumab (RZB) is a humanized monoclonal antibody that specifically blocks the p19 subunit of interleukin 23, which in turn regulates the activation, differentiation, and survival of Th17. RZB has proved their efficacy and their safety compared to anti-TNF. However, studies that assess and compare the improvement in other secondary PROs such as the patient's quality of life are still scarce. Health-related quality of life (HRQoL) is the sum of physical health, well-being, and participation; it defines the functional effect of a disease or its treatment and how it is perceived by the patient. The objective of this paper is to analyze the literature on the impact of treatment with RZB on the quality of life of patients with PSO and their psychological well-being. A bibliographic search was carried out to identify all the papers published from July 2015 to June 1, 2022, on RZB treatment in psoriasis and its impact on health-related quality of life and psychological well-being, finally twenty articles have been evaluated in full text, of which 8 were excluded because they did not meet the inclusion criteria. Risankizumab has shown not only to have very relevant data on effectiveness and safety, but all of this is associated with an improvement in quality of life related to health and psychological well-being measured on generic and specific quality of life scales, both in pivotal trials, ad hoc analysis, and data in real clinical practice.Keywords: Risankizumab, health related quality of life, psoriasis